Mood Structure of Male and Female Teacher’s Talk in the Classroom - Resdilla Pratiwi; Hanifah Oktarina (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
The aim of the study is to describe how mood structures are realized in male and female teachers’ talk in the classroom. A qualitative research was applied where male and female teacher who teach in SMA N I Batahan involved in this research. The data was collected through audio video recording, observation sheet, and taking note. The finding of this study revealed that there are two ways that have been found in realization of mood structure of male and female teachers talk, namely, typical clause mood, and non-typical clause mood. In typical clause mood, there are three ways that have been found, namely statement that realized in declarative mood, then, command that realized in imperative mood, after that question that realized in interrogative mood. Besides that, in non-typical clause mood, it just found two ways in realization of mood structures of male and female teachers’ talk, namely question that realized by modulated declarative, then command is realized by declarative. Based on those, it can be conclude that there is no differences between male and female teachers in realizing mood structure in the classroom.